Fomo Social Anxiety and Phubbing Among Generation Z in Sidoarjo: FOMO, Kecemasan Sosial, dan Phubbing di Kalangan Generasi Z di Sidoarjo - Veronika Afsyia Laurent; Effy Wardati Maryam (Psikologia : Jurnal Psikologi, 2026)
General Background: Phubbing behavior has become increasingly common among Generation Z due to intensive smartphone use and continuous social media engagement. Specific Background: Fear of Missing Out (Fomo) and Social Anxiety are psychological factors associated with excessive smartphone attention during face-to-face interactions. Knowledge Gap: Previous studies have separately examined the association of Fomo or Social Anxiety with phubbing behavior, but limited research has investigated both variables simultaneously among Generation Z. Aims: This study aimed to analyze the relationship between Fomo and Social Anxiety with phubbing behavior among Gen Z in Sidoarjo. Results: This quantitative correlational study involved 384 respondents selected through accidental sampling. Data were collected using validated and reliable scales measuring phubbing, Fomo, and Social Anxiety. Multiple linear regression analysis showed that Fomo and Social Anxiety jointly demonstrated a significant association with phubbing behavior (F = 83.82; p < 0.001) with a contribution of 28.7% (R² = 0.287). Individually, Fomo and Social Anxiety also showed significant relationships with phubbing behavior (p < 0.001). Novelty: This study simultaneously examines Fomo and Social Anxiety as psychological predictors associated with phubbing behavior among Generation Z in Sidoarjo. Implications: The findings highlight the importance of promoting responsible smartphone use, strengthening social interaction awareness, and developing psychosocial education programs addressing Fomo and Social Anxiety among Generation Z.Highlights: Fear of Missing Out showed a significant association with excessive smartphone attention during direct interaction. Social discomfort in face-to-face communication was linked to higher tendencies of ignoring conversation partners. Psychological factors jointly explained 28.7% of behavioral patterns related to smartphone-centered social disengagement. Keywords: Phubbing; Fear of Missing Out; Social Anxiety; Generation Z; Smartphone Use